Robot-assisted oesophagectomy: recommendations towards a standardised Ivor Lewis procedure - Egberts, Jan-Hendrik; Biebl, M.; Perez, D. R.; Mees, S. T.; Grimminger, P. P.; Müller, Beat P.; Stein, H.; Fuchs, H.; Bruns, C. J.; Hackert, Thilo; Lang, H.; Pratschke, J.; et al. (Journal of gastrointestinal surgery, 2019)
A considerable number of reports have been published on the feasibility, techniques, and early postoperative results of robotic-assisted oesophageal surgery. However, these are mostly smaller case series, suggesting that the robot-assisted Ivor Lewis procedure is still in the implementation phase and far from being standardised. Oesophageal surgeons from seven robotic university centres in Germany, experienced in both minimally invasive and robot-assisted minimally invasive surgery, took part in a workshop on robot-assisted surgery. An intensive exchange of opinions and experiences, followed by a step-by-step re-enactment of the operation in a cadaver lab, enabled us to develop a standardised robot-assisted Ivor Lewis surgical workflow, which is presented here. Systematic and objective comparison of experiences and results using a robot-assisted Ivor Lewis procedure has made it possible to develop a standardised surgical workflow that is now clinically applied in our centres. It is hoped that standardisation of this procedure will help to maintain patient safety, prevent medical errors, and facilitate the learning curve, while introducing robotic surgery into a centre.
Gesehen am 28.08.2019